Pilgrimage in the digital age - Brumec, Snežana (Edinost in dialog, 2025)
The Camino de Santiago has emerged in late modernity as a ritual space where diverse spiritual, religious, and secular orientations converge. This article explores the Camino as a site of spiritual pluralism and self-transcendence, highlighting its transformative potential for pilgrims independent of doctrinal belief. Drawing on empirical studies, we demonstrate that the pilgrimage experience fosters exceptional human experiences (EHEs), personal growth, and a shift in values toward universalism and benevolence. Embracing an integrative perspective on spirituality, we propose a framework for designing ethically grounded, AI-guided pilgrimage companions that support rather than commodify the journey. Instead of serving merely logistical functions, such AI systems can nurture reflection, facilitate encounters with diverse spiritual perspectives, and reinforce the Camino’s communitarian and existential ethos. This vision invites further interdisciplinary research on how digital tools can enhance spiritually meaningful human experiences.
Keywords: AI and spirituality; Camino de Santiago; duhovna transformacija; integrative perspective; integrativna perspektiva; pilgrimage; romanje; spiritual transformation; umetna inteligenca in duhovnost